Pengaruh Keberagaman Produk dan Lokasi terhadap Niat Beli di UD. Jesron - Elijon Tumanggor; Tino Osama Munthe; Juwita Sihotang; Bayu Teta (Jurnal Bisnis Inovatif dan Digital, 2025)
This study aims to determine the effect of product diversity and location on consumer purchase intention at UD Jesron. This research uses a quantitative approach with a survey method through questionnaires distributed to 40 respondents who have purchased products at UD Jesron. Data were analyzed using validity tests, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with the help of SPSS version 25. The results showed that product diversity had no significant effect on purchase intention (sig. 0.849 > 0.05), while location had a positive and significant effect on purchase intention (sig. 0.010 < 0.05). Simultaneously, both variables significantly affected purchase intention with a significance value of 0.000 < 0.05. The coefficient of determination indicates that 33.8% of the variation in purchase intention is influenced by product diversity and location, while the rest is influenced by other variables outside the model. Based on these findings, it is suggested that UD Jesron should optimize its business location and implement appropriate marketing strategies for its products.